Advanced Computer Training Course: An initiative towards enhancing the skill of Visually Impaired Persons- A part of CSR Program (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
People are getting more aware about the  potential capabilities of a visually impaired  person. Thus, with the growing awareness of the  abilities of the visually impaired population, few  business houses are coming forward in including  a visually impaired person in their workforce. Advanced Computer Training Course(ACTC)  conducted by TCS, as a part of their CSR  program, to empower the visually impaired  population is one of its kind initiative. Through this paper the researcher aims to analyse  the efficiency of CSR programme in empowering  the visually impaired population, by conducting  survey on 60 trainees from Mumbai centre. The  findings states that there has been a significant  improvement on the employment front after  the training program. It is noteworthy that as  much as 60% of the trainees were unemployed  prior to the training, against a mere 33.3%  unemployment post the training.
Keywords: Bibliometric; Financial Planning; Retirement; Investment; Saving